931 Deep Inferior Epigastric Perforator (DIEP) Flap: Impact of Early Drain Removal on Seroma Formation Rate and Duration of Inpatient Stay. (12th October 2021) - Grigg, K; Clancy, R; Lewis, C; Jackson, P
Abstract: Aim: Donor site seroma can follow deep inferior epigastric flap (DIEP) harvest. Post-surgery gradient technology (GTC) garments are worn by DIEP patients postoperatively following drain removal to reduce seroma formation. Early drain removal was considered a contributing factor to increased seroma formation rate. From June 2018 drain removal regardless of output was instigated at day two post-surgery. Prior to this, drains were removed when less than 30mls over 24 hours. We aim to assess the seroma rate post DIEP harvest with early drain removal. Method: Retrospective review of prospectively managed database between June 2018 to May 2020. Surgical complications and length of stay in hospital were recorded. Results: 200 patients underwent DIEP flap breast reconstruction. The mean age of patients was 52 years (range 28-73). There was no significant difference in seroma complication rate between those who had drains removed on day 3 compared with day 2 ((1.02% (1/98) vs. (0.98% (1/102); p = 1). The mean length of stay in hospital for the 1st cohort was 3.86 days and for the 2nd cohort was 3.23 days. There were no complications related to drain removal. Conclusions: Our data suggests that drain removal after 2 days postoperatively with DIEP reconstruction does not affect seroma complication rates. Moreover, it leads to a shorter hospital stay. These conclusions are in keeping with enhanced recovery protocols and an early drain removal surgical process could be advised.